Transformation of Dependent Rights In The Digital Era A Study In Electronic Implementation - Waradatun Nafi’ah; Arofa; Andianita Nur Ilahiyah; Moh Basri; Ahmad Musadad (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
The digitization of the dependent rights system is an innovation in land administration that aims to increase efficiency, transparency, and legal certainty in Indonesia. The implementation of Electronic Dependent Rights (HT-el) brings various benefits, such as a faster registration process, wider access, and minimal administrative errors compared to conventional systems. However, in its implementation, there are still various obstacles, such as limited technological infrastructure, low public digital literacy, and challenges in maintaining data security and user privacy. This study uses normative juridical methods, utilizing legal and conceptual approaches to examine the effectiveness of regulations regarding electronic liens. The findings of the study suggest that although HT-el has significant promise to improve land services, additional strategies are essential. This includes strengthening regulations, improving infrastructure, and engaging with the community. These measures are necessary to ensure the optimal implementation of this system and to provide legal certainty for all stakeholders involved.